Federalismo fiscal, endividamento público e descentralização: a experiência comparada de Brasil e Colômbia - Alejandro Angel Tapias (2008)
This Masters dissertation studies the intergovernmental relations in Brazil and Colombia, from a comparative perspective. The objective of the research is to study the role that the debt had in the processes that the intergovernmental relations had in both countries aforementioned, having as reference, the constitutional change occurred in both of them. In the first place, it does a theoretical approach to the intergovernmental relations and the strong link with the political and economic systems of the Nation States, making special emphasis in the core instruments of economic policies, such as, the budget as an expenses organizer and the debt as an intertemporal distributor of resources.With such theoretical frame, it seeks to analyses the process that the Brazilian and Colombian intergovernmental relations had for the five decades between 1960 and 2008, having as the core, the role that the debt had in the institutional developments that included within the period, new Constitutions.Even if these processes had been idealized as instruments of transformation of the intergovernmental relations, the respective Constitutions did not modify these in the expected dimension, and, despite of the enthusiasm generated by this democratic openness, the dynamic of the Brazilian and Colombian intergovernmental relations returned rapidly to the patterns that previously ruled such relations.The comparative perspective allows to establish some common challenges faced by both societies, with special emphasis, in the increasingly marginal role of the intermediate level governments, Brazilian states and Colombian departments, in the public policy process; nevertheless, it also exists cooperation opportunities among the different governments of all levels in order to implement public policies that uses the strengths of each of them.